Looking into the prevalence of bycatch juveniles of critically endangered elasmobranchs: a case study from pelagic longline and trammel net fisheries of the Asinara Gulf (western Mediterranean) - Scacco, Umberto; Gennari, Enrico; Di Crescenzo, Simone; Fanelli, Emanuela (Frontiers in Marine Science, 2023)
Bycatch of cartilaginous species is considered one of the main drivers for the dramatic declines observed in many populations. Pelagic longlines and passive nets impact many species depending on their life stage and habitat use. Here, we present an updated list of incidental catches collected through a 4-year fishery-dependent survey. We documented the bycatch of four critically endangered species, particularly 13 individuals of Isurus oxyrinchus, Prionace glauca, and Mobula mobular by longlines and one specimen of Lamna nasus by trammel nets in the Asinara Gulf (Northern Sardinia, Italy). As almost all specimens were juveniles or newborns, we explored and discussed the potential drivers explaining their prevalence in the sample. Despite our low sample size, of the four possible options discussed, the role of the Asinara Gulf as an Important Shark and Ray Area (ISRA) for large pelagic elasmobranch species is one worth considering.